Demarketing an iconic national park experience: Receptiveness of past, current and potential visitors to selected strategies. (March 2019) - Weiler, Betty; Moyle, Brent D.; Scherrer, Pascal; Hill, Madeline
Abstract: Tourism in national parks is essentially about providing memorable nature-based experiences for visitors. However, often there are limits to the numbers of people that can enjoy an iconic experience at a given site in a national park. Summiting a mountain has the propensity to provide an iconic experience for visitors but can be accompanied by management issues, including visitor safety, environmental impacts and even cultural sensitivities. While there are a range of possible management interventions, one approach is to actively demarket the experience. Published studies on the demarketing of national parks to date have primarily been conceptual, with limited empirical research exploring stakeholders' perceptions of available strategies and virtually no research on visitor perceptions. This manuscript assesses the receptiveness of past, current and potential visitors to demarketing an iconic experience, specifically summiting Wollumbin - Mount Warning, Australia. Findings from an on-site survey of visitors (n = 794) and an on-line survey of past, current and potential visitors (n = 990) revealed some potential for the use of access fees to demarket the summit experience. While there was also some support for additional experiences to complement the summit option, current visitors noted they were still likely to climb the peak. Higher levels of receptiveness to modified and alternative experiences were apparent among past and potential visitors. To reduce numbers on the summit of Wollumbin – Mount Warning, demarketing needs to be used with a suite of other management strategies. This manuscript's successful application of the marketing mix framework for inventorying demarketing strategies can serve as a model for other park contexts. Future research should extent the work to other contexts and to an exploration of the perceived benefits and costs of a wider range of demarketing strategies. Management implications: Better understanding and control of the media and messages communicated about particular park experiences pre-visit Use of pricing together with modified experience options to demarket experiences to current visitors Development, testing and promotion of alternative experiences to demarket visitor experiences to potential visitors Stakeholder consultation that prioritizes Indigenous cultural values Demarketing that is grounded in and aimed at facilitating sustainable visitor management